Answer:
3 to the powered of 7
Step-by-step explanation:
Answer: -6
Multiply 3 by -2 first =-6 inside brackets
Original 6 inside brackets plus -6 from performing multiplication problem inside the brackets equals 0, so you now have 0 minus the original -6 which equals -6 overall
Step-by-step explanation:
Triangle ABC and triangle DCE are congruent, so line DE = line AB
Use the cosine rule to find angle ACB
![52.2^{2}= 50^{2}+ 70^{2}-(2*50*70*cos(ACB))](https://tex.z-dn.net/?f=%2052.2%5E%7B2%7D%3D%2050%5E%7B2%7D%2B%20%2070%5E%7B2%7D-%282%2A50%2A70%2Acos%28ACB%29%29%20%20%20%20)
![2724.84=7400-(7000cos(ACB))](https://tex.z-dn.net/?f=2724.84%3D7400-%287000cos%28ACB%29%29)
![2724.84-7400=-7000cos(ACB)](https://tex.z-dn.net/?f=2724.84-7400%3D-7000cos%28ACB%29)
![-4675.16=-7000cos(ACB)](https://tex.z-dn.net/?f=-4675.16%3D-7000cos%28ACB%29)
![\frac{4675.16}{7000}=cos(ACB)](https://tex.z-dn.net/?f=%20%5Cfrac%7B4675.16%7D%7B7000%7D%3Dcos%28ACB%29%20)
![Angle ACB= cos^{-1} ( \frac{4675.16}{7000})](https://tex.z-dn.net/?f=Angle%20ACB%3D%20cos%5E%7B-1%7D%20%28%20%5Cfrac%7B4675.16%7D%7B7000%7D%29%20)
Angle ACB = 48.1°
Evaluating the given sequence, it is evident that the next number is twice the number prior to it. Thus, the given is a geometric sequence with first term (a1) equal to 1 and common ratio of 2. The geometric series may be calculated by the equation,
Sn = a1 x (1 - r^n) / (1 - r)
where Sn is the sum of n terms in this case, n = 11.
Substituting the known values,
<span> Sn = 1 x (1 - 2^11) / (1 - 2) = 2047
</span>
Thus, S11 is 2047.
Answer:
n=6
Step-by-step explanation:
(n-18)/3 = -4
multiply by 3
n-18 = -12
add 18
n = 6